Socialno omrežje kot okvir upravljanja s kakovostjo življenja in spemembe v Sloveniji med letoma 1987 in 2002 - Mandič, Srna (Družboslovne razprave, 2005)
Community networks and personal networks of social support are seen as two different frameworks allowing individuals to manage the quality of their life; the most relevant functions of social networks are an exchange of goods and services, information processing and problem solving. We argue that duringthe Slovenian "transition" the community networks proved much less responsive than the networks of social support. For evidence, a number of findings by Slovenian analysts are summarized and some empirical data evaluated. A number of explanatory factors is pointed out and some particular social circumstances identified, which proved to have been more favorably inclined to the development of personal networks of social support and also articulation and solving of individual problems rather than those of communities.
Keywords: Slovenia; Slovenija; socialna država; welfare state; družbena omrežja; družbeni odnosi; medosebni odnosi; kvaliteta življenja; življenjski standard